Structural effects of the active site mutation cysteine to serine in Bacillus cereus zinc-beta-lactamase. - Chantalat, L. (Cold Spring Harbor Laboratory Press, 2000)
Beta-lactamases are involved in bacterial resistance. Members of the metallo-enzyme class are now found in many pathogenic bacteria and are becoming thus of major clinical importance. Despite the availability of Zn-beta-lactamase X-ray structures their mechanism of action is still unclear. One puzzling observation is the presence of one or two zincs in the active site. To aid in assessing the role of zinc content in beta-lactam hydrolysis, the replacement by Ser of the zinc-liganding residue Cys168 in the Zn-beta-lactamase from Bacillus cereus strain 569/H/9 was carried out: the mutant enzyme (C168S) is inactive in the mono-Zn form, but active in the di-Zn form. The structure of the mono-Zn form of the C168S mutant has been determined at 1.85 A resolution. Ser168 occupies the same position as Cys168 in the wild-type enzyme. The protein residues mostly affected by the mutation are Asp90-Arg91 and His210. A critical factor for the activity of the mono-Zn species is the distance between Asp90 and the Zn ion, which is controlled by Arg91: a slight movement of Asp90 impairs catalysis. The evolution of a large superfamily including Zn-beta-lactamases suggests that they may not all share the same mechanism.